2022
DOI: 10.1038/s41598-021-03997-z
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with nonrestorative short sleep or nonrestorative long time-in-bed in middle-aged and older adults

Abstract: Associations of sleep duration with human health could differ depending on whether sleep is restorative. Using data from 5804 participants of the Sleep Heart Health Study, we examined the longitudinal association of sleep restfulness combined with polysomnography-measured total sleep time (TST) or time in bed (TIB), representing different sleeping behaviors, with all-cause mortality. Among middle-aged adults, compared with restful intermediate TST quartile, the lowest TST quartile with feeling unrested was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…39 Nonetheless, our findings were similar to those of a research that evaluated the association between objective sleep duration and mortality risk. 40 We also showed that the reproducibility of sleep duration assessments based on self-reporting was moderate in this older cohort population; thus, the evaluations of sleep duration were likely to be relatively stable. Second, as the sleep status assessments were conducted only at baseline, participants' sleep status may have changed A c c e p t e d V e r s i o n 17 during the follow-up period.…”
Section: Strengths and Limitationsmentioning
confidence: 64%
“…39 Nonetheless, our findings were similar to those of a research that evaluated the association between objective sleep duration and mortality risk. 40 We also showed that the reproducibility of sleep duration assessments based on self-reporting was moderate in this older cohort population; thus, the evaluations of sleep duration were likely to be relatively stable. Second, as the sleep status assessments were conducted only at baseline, participants' sleep status may have changed A c c e p t e d V e r s i o n 17 during the follow-up period.…”
Section: Strengths and Limitationsmentioning
confidence: 64%
“…Subjective sleep restfulness has begun to attract attention as a predictor of mortality risk. 30 Sleep quality can influence mental and physical outcomes such as depression, 31 academic performance, 32 and fatigue. 33,34 Although sleep duration is also an important indicator, sleep quality is more useful as a subjective measure to predict health because subjective sleep duration often does not coincide with actual sleep duration, excluding bedtime.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective sleep restfulness has begun to attract attention as a predictor of mortality risk. 30 Sleep quality can influence mental and physical outcomes such as depression, 31 academic performance, 32 and fatigue. 36 In the current study, participants with high subjective sleep quality exhibited a higher frequency of AE and a longer duration of PR, but the daily step count and RE were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…While physiological sleep need may decrease with age, there is no clear reduction in time in bed 57 , suggesting excessive time in bed relative to physiological sleep need in older adults. Epidemiological evidence suggests that objective longer time in bed is associated with higher total mortality in older adults independent of objective sleep duration per se 17 , 58 . In addition, there is evidence linking objective long time in bed and self-reported long sleep duration 59 .…”
Section: Discussionmentioning
confidence: 99%